The Effectiveness of Instagram "Studyin.Japanese" to Improve Japanese Vocabulary Skills of Intermediate Level Japanese Language Department UMY'S Students - Rosi Rosiah (Chi'e: Journal of Japanese Learning and Teaching, 2023)
This study aimed to measure the effectiveness of the "studyin.japanese" Instagram account as a learning medium for improving Japanese vocabulary skills. This research uses quantitative methods with a purely experimental research design. The sample of this study was 30 students of the PBJ UMY Study Program level 2 for the 2021/2022 academic year. Data is collected through questionnaires and tests. The test results showed that the average value of the experimental control group was smaller than the average value of the control groTherehere was no significant difference between the experimental and control groups' learning outcomes. Furthermore, the results of calculating the effectiveness of learning in the experimental group with the N-gain formula were obtained at 0.116, which means that using the Instagram media "studyin.japanese" is not practical in learning Japanese Vocabulary. While the N-Gain control class is 0.512 which means the use of PowerPoint media is effective in learning Japanese Vocabulary. So it can be concluded that using conventional media is still more effective than using Instagram media "studyin.japanese" in learning Japanese Vocabulary. However, based on the results of the questionnaire, students gave a positive response. All respondents strongly agreed that "studyin.japanese" media in learning Japanese Vocabulary can be an alternative medium for learning Japanese Vocabulary. Students feel motivated and easy to memorize Japanese Vocabulary.